Application of computer navigation technique in the treatment of complex orbital fractures - Jiong Liu (Guoji Yanke Zazhi, 2020)
AIM: To evaluate the efficacy and utility of computer navigation technique in the treatment of complex orbital fracture. METHODS: A retrospective review of 19 patients with complex orbital fractures were conducted. They underwent the reconstructive surgery assisted by image-data-based computer navigation. The pre- and postoperative data of enophthalmos, eyeball movement, diplopia, infraorbital numbness, and orbit CT image were recorded and analyzed. RESULTS: The processes of pre-operation planning and intraoperative navigation were successful. During the 6 to 18mo postoperative follow-up, enophthalmos was completely corrected in 14 cases, while 5 patients had slight residual enophthalmos. Eyeball movement restriction was completely corrected in 7 cases, and was also improved in 3 cases. Diplopia was disappeared in 10 patients and improved in 2 patients, but still maintained in 1 patient postoperatively. Infraobital numbness was found in 4 cases, and dissappeared in 6mo postoperatively. No serious complications such as optic nerve lesion and vision loss were observed. Postoperative CT scans demonstrated that the fractures were corrected in all cases. The accuracies of the surgeries were satisfying. CONCLUSION: Computer navigation system is a safe and effictive technique in assisting diorthosis in complex orbital fracture.